Analisis Implementasi Digital Banking dalam Peningkatan Kualitas Layanan pada Bank Bri Unit Unpatti Ambon - La Pirwan Sampulawa; Kevin Hermanto Tupamahu; Syahrina Noormala Dewi (Jurnal Pendidikan Ekonomi, 2025)
The rapid advancement of information technology has driven a transformation in banking services through digital banking, offering customers greater accessibility and transaction efficiency. This study aims to analyze the implementation of digital banking at BRI Unit Unpatti Ambon and to identify the barriers and solutions applied to improve service quality. The research employed a qualitative descriptive approach with data collected through interviews, observations, and documentation. Findings reveal that the adoption of digital banking, particularly through BRImo services and supporting facilities, enhances customer satisfaction, accelerates transaction processes, and strengthens user loyalty. The main challenges identified include limited digital literacy, especially among elderly customers, inadequate internet access in certain regions, and rising cybersecurity risks. These results highlight the necessity of training programs for employees and customers, expansion of internet infrastructure, and strengthening of internal security systems. This study provides new insights into how digital banking can enhance service quality in a local context while offering practical recommendations for sustaining digital banking innovation in Indonesia.